Can I Give Them Back Now? : The Aargh to Zzzz of Parenting - Simmons, Joanna and Curtis, Jay (London Square Peg, 2009)
Can I Give them Back Now?' puts two fingers up to the pervasive notion that parenthood is an eternally rewarding experience. Taking a wry, down-to-earth and humorous look at life with young children, it taps into the very normal, but hard-to-admit ambivalence that so many parents feel about raising kids.--Publisher.
Keywords: Parenting